P318 Association between faecal calprotectin values and infliximab trough levels in inflammatory bowel disease patients. (16th January 2018) - Rodriguez Alonso, L; Serra, K; Santacana, E; Padullés, N; Arajol, C; Gilabert, P; Orobitg, J; Rodríguez-Moranta, F; Colom, H; Padullés, A; Bas, J; Guardiola, J
Abstract: Background: Serum Infliximab (IFX) trough levels (Cmin) have been associated with clinical response. Therapeutic drug monitoring of IFX has been shown to be clinical and cost-effective in inflammatory bowel disease (IBD) patients. However, some patients present clinical symptoms while IFX Cmin >3 mg/l. Activity markers such as fecal calprotectin (FCP) in combination with IFX Cmin could be of clinical utility to optimise therapy in IBD patients. The aim of this study was to evaluate the relationship between FCP and IFX Cmin, in IBD patients receiving maintenance IFX. Secondary analysis: (i) to determine the use of IFX Cmin as a clinical predictor of FCP < 250 μg/g and (ii) to assess the discriminate ability of FCP to predict subtherapeutic Cmin IFX (Cmin < 3 mg/l) by ROC curve. Methods: Prospective study of IBD patients receiving IFX between January 2014 and February 2017. Patients provided: (a) blood samples drawn immediately before IFX infusion to determine IFX Cmin and (b) fecal samples within the same IFX cycle of administration to determine FCP. ROC curves (Receiver Operating Characteristic) were used to assess the discriminative ability of IFX Cmin to predict FCP < 250 μg/g and discriminative ability of FCP to predict IFX Cmin < 3 mg/l. Pharmacokinetic and statistical analysis was performed using Nonmem®7.3 and SPSSv19, respectively. Results: A total of 89 patients (46.1% women/ 53.9% men) were included. A total of 188 faeces and blood samples were analysed. Median FCP: 233 μg/g (P25–P75: 77–1225). In 97 samples (51.6%), FCP was <250 μg/g. Median Cmin: 4.1 mg/l (P25–P75: 1.9–6.9). Median IFX Cmin when FCP < 250 μg/g vs. FCP≥250 μg/g group was 4.7 mg/l (Cmin ≥3 mg/l: 36%) vs. 3.62 mg/l (Cmin ≥3 mg/l: 28%), respectively ( p = 0.043). The area under the ROC for Cmin IFX to predict FCP < 250 μg/g was 0.586 (IC95%: 0.504–0.667) and for FCP to predict Cmin<3 mg/l was 0.596 (IC95%: 0.509–0.683). Conclusions: Significantly higher IFX Cmin were observed when FCP < 250 μg/g compared with FCP ≥ 250 μg/g (4.7 mg/l vs. 3.62 mg/l). Also, percentage of samples with Cmin ≥ 3 mg/l is higher when FCP < 250 μg/g vs. FCP ≥ 250 μg/g (36% vs. 28%). Given the relationship between FCP and IFX Cmin, refinement of current pharmacokinetic models by including fecal calprotectin as a measure of the inflammatory burden could potentially improve their performance.